Analisis Green History sebagai upaya menumbuhkan kesadaran lingkungan melalui buku Teks Sejarah Wajib kelas X (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2025)
History textbooks are part of classroom learning. Textbooks contain character content such as environmental love that fits with SDGs. Green history in history textbooks has not been studied. This study aims to describe how the analysis of green history in the Indonesian history textbooks for 10th grade written by Restu Gunawan (2017 revised edition) based on the 2013 Curriculum which includes urgency of green history in the history textbooks and form of exposure to green history elements in textbook. The reseacrh method used is quantitative content analysis method based on the stages of research expressed by Krippendorff, namely unitizing, sampling, coding, data simplification (reducing), conclusion based analysis (inferring), and narrating answer to research question. Through content analysis that has been carried out on mandatory history textbooks, green history has an important enough urgency to be included in textbooks as an effort to include green history elements that must be included in textbooks by looking at the importance of green history in increasing environmental awareness through intelligence. The results of the overall content analysis show that green history elements have been found in history textbooks with various forms of sentences in the main narrative or practice questions that are felt to be able to explain to students the form of environmental change from time to time through historical events.
Keywords: Green History; History Textbook; History Learning